Sintesis Ferri Salen-Taeniolit Sebagai Katalisator Pada Reaksi Pembentukan Monomer Poli Karbonat - Alimuddin, Alimuddin; Agusriyadin, Agusriyadin; Syahrir, Syahrir; Kadir, Laode Abdul (Al-Kimia, 2021)
The researcher has succeeded in synthesizing the Ferri Salen-Taenolite complex as a clay based catalyst and applying it to the reaction of glycerol carbonate formation. Lewis acidity of the catalyst complex can increase through the immobilization process in addition, the activity and selectivity of the catalyst also increase. The formation of salene ligands is shown by the appearance of the peak C=N at the wave number around 1640 cm-1 and the O-H peak around 3400 cm-1. The formation of the Fe(salen)NO3 complex is indicated by the reduction of the vibration intensity O-H at the wave number of about 3400 cm-1 and the shift of the peak C=N in the area around 1640 cm-1 to 1690 cm-1. The complex [Fe(salen)]NO3 has been synthesized with physical properties in the form of brown powder and effective magnetic moment by 2,197 BM. The complex [Fe(salen)] + was successfully immobilized into the LiTN as much as 9.12 mmol/g LiTN. Based on the catalytic activity test, the catalyst was active in the reaction of polycarbonate monomer formation which is indicated by a change in vibration of the urea carbonyl (CO amine) group at wave number 4242 cm-1 to vibrate the carbonyl group (CO ester) at wave number 1786 cm-1 which indicates that glycerol carbonate has been formed.